Semiotic Diagnostics: Methodology for Measuring Education Transformation Efficiency - N. A. Lyurya (Moscow Polytechnic University, 2020)
Education restructuring projects require efficiency criteria for the assessment and monitoring of management efforts to achieve set goals. The article focuses on understanding the efficiency itself and the essence of its assessment. The key points of formation and methodological innovations of the presented concept of diagnostics which substantiates the relevance are discussed: interpretations of education systems as semiotic systems; management of the transformation of education systems based on the measurement of the parameters of the order of self-organization of complex open systems; selecting, as a control parameter, the order of the characteristic "information efficiency". This characteristic makes it possible to implement a procedure for measuring two competitive interactions: the process of selecting the optimal ways to achieve an asymptotically distant goal and the process of the competition of semiotic attractors as an expression of asymptotic goals. The specificity of self-organization mechanisms puts forward requirements for managing these processes. These requirements are the need to conduct such a selection which does not cut off other paths to other goals but changes the hierarchy in the subordination of ways to achieve goals. Ignoring the requirement leads to the selection out of "one" path. Conclusions regarding the determination of the place of pedagogical education in the context of modernization of the entire system of national education are drawn. Firstly, the implementation of technologies that demonstrate their efficiency in foreign experience into the practice of national education should be guided by the fact that this efficiency was obtained to achieve substantially different goals. Secondly, the implementation of innovative educational technologies in teacher training should be ahead of this implementation in teaching practice at all educational levels, which will ensure that the advantages of these technologies are effectively tuned to achieve the goals of national education.